Assessing the Efficacy of Test-Optional Policies in Enhancing Socio-Demographic Diversity in Higher Education Institutions - Kai Cui; Liangchen Mei; Changrong Du (Journal of Advanced Research in Education, 2023)
This study offers a comprehensive analysis of the interplay between standardized testing and the burgeoning holistic admissions approach within higher education admissions. We systematically examine the inherent biases present in standardized tests—spanning economic, racial, linguistic, and cultural sectors—and their potential implications for widening socio-demographic disparities. Utilizing the University of California system as a case study, the paper contrasts this with the holistic admissions approach which endeavors to encapsulate a multifaceted perspective of prospective students by factoring in both academic milestones and personal narratives. While this approach emerges as a promising alternative, we also discuss its innate challenges, especially concerning ensuring objectivity and uniformity. By evaluating these methodologies within the contemporary admissions ecosystem, the study emphasizes the urgency for transformative admissions strategies that champion both diversity and equity. In the realm of higher education admissions, the efficacy and equity of standardized testing have long been subjects of contention. Initially designed to provide a uniform measure of student achievement, these tests are now under scrutiny for potentially perpetuating socio-demographic disparities. As institutions grapple with the implications of such biases, there’s a growing inclination towards more holistic admissions approaches that aim to capture the multifaceted nature of a student’s potential. This paper delves into the inherent challenges and biases of standardized tests, examines the nuances of the holistic admissions approach, and explores the interplay between the two in the modern admissions landscape.